Poly(2,5-benzimidazole)/sulfonated sepiolite composite membranes with low phosphoric acid doping levels for PEMFC applications in a wide temperature range - Xiaoxiao Zhang; Qingting Liu; Lei Xia; Dongyang Huang; Xudong Fu; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao (2018)
o broaden the operating temperature range of phosphoric acid (PA) doped polybenzimidazole membrane-based proton exchange membrane fuel cells (PEMFCs) toward low temperatures, a novel series of poly(2,5-benzimidazole) (ABPBI)/sulfonated sepiolite (S-Sep) composite membranes (ABPBI/S-Sep) with low PA doping levels (DLs) were prepared via in-situ synthesis. The desirably enhanced mechanical, thermal, and oxidative stabilities of ABPBI/S-Sep composite membranes were achieved by constructing ABPBI chains arranged along the sepiolite (Sep) fibers and acid-base crosslinks formed between S-Sep fibrous particles and ABPBI chains. Benefiting from the richness of high temperature stable bound water and the excellent water absorbability of Sep particles that enable the formation of additive proton conducting paths, the composite membranes retained bounded PA and achieved much higher proton conductivities under both anhydrous and hydrous conditions compared to PA-doped ABPBI membranes. Proton conductivity values above 0.01 S/cm at 40-90 °C/20-98% RH conditions and 90-180 °C/anhydrous conditions as well as peak power density of 0.13 and 0.23 W/cm2 at 80 and 180 °C with 0% RH, respectively from the ABPBI/2S-Sep composite membrane are more holistic compared to Nafion at low temperatures and polybenzimidazole-based membranes at high temperatures, respectively. The excellent properties of ABPBI/S-Sep composite membranes suggest them as prospective candidates for PEMFCs applications in a wide temperature range.